Smart Government Melalui Transaksi Pembayaran Sistem Barcode Di Pasar Pabaeng-Baeng Kota Makassar - Saputri, Andi Iin; Madani, Muhlis; Abdi, Abdi (Universitas Muhammadiyah Makassar, 2021)
This study purposed to determine Smart Government through transaction Barcode Payment System at Pabaeng-baeng Market, Makassar City. Smart Government referred to the implementation of ICT ini public service in the field governance effectively. Meanwhile, Smart City in addition to covering administration government also deals with health services, transportation, education, and soon. The number of information in this study were 08 people. This study used qualitative with the type of phenomenological research that emphasized on the subjectivity of human life experience. Data collection techniques used methods of observation, interview and documentation. Data analysis used interactive analysis model. The result showed that Smart Government Through Barcode System Payment transaction at the Pabaeng-baeng Market in Makassar City had not fully implementation optimally this could be seen from the aspect of the Smart stage. Governtment through the payment transaction of the Barcode System in Pabaeng-baeng Market. This could be seen from the indicators (1) Simple (2) Moral (3) Reseponsiviness and (4)Transparaency. Keyword: Smart Governtment, Barcode System